Barbados : 2008 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2008)
Barbados's 2008 Article IV Consultation is focused on policies to balance the conflicting risks to inflation, growth, and medium-term sustainability. Although the government has maintained some policy space by postponing the liberalization of the capital account, its options are constrained by high public debt and the peg to the U.S. dollar. Downward-trending annual inflation rates masked pent-up price pressures that have been unleashed. The government stressed its commitment to fiscal prudence, with a view to balancing the central government accounts over the medium term.